Development and Evaluation of Nanoemulsifying Preconcentrate of Curcumin for Colon Delivery - Jyoti Wadhwa; Abhay Asthana; Gyati Shilakari; Arun Kumar Chopra; Ranjit Singh (The Scientific World Journal)
The present study aimed to develop and optimize a nanoemulsifying preconcentrate formulation of curcumin with good emulsification ability and optimal globule size, for controlled targeting in colon. Content of formulation variables, namely, X1 (Peceol), X2 (Cremophor-EL), and X3 (Transcutol HP), were optimized by Box-Behnken design of experiments for its impact on mean globule size (Y1), emulsification time (Y2), and time required for drug release (85%) in phosphate buffer (pH 7.2), t85% (Y3). Transmission electron micrographs confirmed that there is no coalescence among globules, with size range concordant with the globule size analysis by dynamic light scattering technique (100 nm). 3D plots indicated that concentration of formulation ingredients significantly influences the formulation properties (globule size, emulsification time, and drug release). In vitro release profile (in phosphate buffer; pH 7.2) represents the fact that more than 50% of the drug was released within initial 15 min whereas in vivo release showed limited systemic absorption (Cmax 200 ng/mL) of curcumin. Stability study ensures the protection of drug in alkaline media which may further confirm the localised delivery of drug to colonic region. Study demonstrated that the nanoemulsifying preconcentrate can be a promising system for the colon specific delivery of curcumin to treat local pathologies.